PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA DI PT TRIO MOTOR HONDA WAREHOUSE BANJARMASIN - Mailiana Mailiana; Diana Hayati; Siti Rahayu (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2018)
Abstract, This research aims to examine the effect of work discipline on employee performance at PT Trio Motor Honda Warehouse Banjarmasin. Subjects in this study were as many as 40 people. According to Arikunto (1998; 120) that